Differences in glucocorticoid use in childhood vasculitis - Ünal, Dilara; Bilginer, Yelda (Acta Medica, 2024)
This review aimed to explore the differences in glucocorticoid use across various subtypes of childhood vasculitis, focusing on their effectiveness, potential side effects, and tapering strategies to minimize toxicity. A comprehensive review was conducted to evaluate the clinical applications of glucocorticoids in pediatric vasculitis subtypes. Recommendations from recent studies and guidelines were assessed, focusing on glucocorticoid protocols for conditions such as IgA vasculitis, Kawasaki disease, polyarteritisnodosa, ANCA-associated vasculitis, and Takayasu arteritis. Glucocorticoid tapering strategies and toxicity indices, such as the Pediatric Glucocorticoid Toxicity Index (pGTI), were also analyzed. Glucocorticoid use varied across vasculitis subtypes. For IgA vasculitis, mild cases were managed with oral prednisolone, while severe nephritis required intravenous methylprednisolone and immunosuppressants. In Kawasaki disease, corticosteroids were used for refractory cases alongside IVIG and aspirin. Severe polyarteritis nodosa cases showed better outcomes with cyclophosphamide and high-dose glucocorticoids, whereas non-severe cases benefitted from low-dose glucocorticoids and NSAIDs. ANCA-associated vasculitis studies reported no significant correlation between glucocorticoid dose and outcomes, although side effects were dose-dependent. In Takayasu arteritis, children generally received lower doses than adults, based on adult treatment guidelines. The pGTI was highlighted as a valuable tool to monitor and assess glucocorticoid toxicity in pediatric patients. Glucocorticoids remain a cornerstone of treatment in pediatric vasculitis, but their use must be carefully tailored to balance efficacy and toxicity. Early tapering and transitioning to alternative therapies, when feasible, are critical to minimizing adverse effects.